Climate-related child undernutrition in the lake Victoria basin: an integrated spatial analysis of health surveys, ndvi, and precipitation data - Lopez-Carr, David Lawrence; Mwenda, Kevin M.; Pricope, Narcisa G.; Kyriakidis, Phaedon; Jankowska, Marta M.; Weeks, John R.; Funk, Chris C.; Husak, Gregory J.; Michaelsen, Joel C. (My University, 2016)
Despite growing research into the socio-economic aspects of vulnerability [1]-[4], relatively little work has linked population dynamics with climate change beyond the complex relationship between migration and climate change [5]. It is likely, however, that most people experience climate change in situ, so understanding the role of population dynamics remains critical. How a given number of people, in a given location and with varying population characteristics may exacerbate or mitigate the impacts of climate change or how, conversely, they may be vulnerable to climate change impacts are basic questions that remain largely unresolved [6]. This paper explores where and to what extent population dynamics intersect with high exposure to climate change. Specifically, in Eastern Africa's Lake Victoria Basin (LVB), a climate change/health vulnerability hotspot we have identified in prior research [7], we model child undernutrition vulnerability indices based on climate variables, including proxy measures (NDVI) derived from satellite imagery, at a 5-km spatial resolution. Results suggest that vegetation changes associated with precipitation decline in rural areas of sub-Saharan Africa can help predict deteriorating child health.
Keywords: Climate; Lake Victoria Basin (LVB); Stunting; Undernutrition; NDVI; Vulnerability